Evaluation of Muscodor cinnamomi as an egg biofumigant for the reduction of microorganisms on eggshell surfaces and its effect on egg quality - Suwannarach N. (2017)
© 2017 Elsevier B.V. The presence of microorganisms on the eggshell surface is a factor of consideration in determining egg quality. These microorganisms can contribute to egg spoilage and can infect the egg. In this study, 18 morphotypes of microorganisms were isolated from eggshells. Morphological, biochemical, physiological and molecular analyses were used to identify these morphotypes into 7 species; Bacillus drentensis, Staphylococcus arlettae, Stap. cohnii, Stap. kloosii, Stap. saprophyticus, Stap. sciuri and Stap. xylosus. The potential of Muscodor cinnamomi to reduce the presence of microorganisms on eggshells by biological fumigation was investigated. The result showed that 16 strains of the tested microorganisms were inactivated after the exposure of the fungal volatile organic compounds. The most abundant compound was 2-methylpropanoic acid, followed by 3-methylbutan-1-ol. Our results indicated that a 24-h period of fumigation of 100 g rye grain culture of M. cinnamomi was the minimum dose that could significantly reduce the number of microorganisms on the eggshell surface. Fumigated eggs from both box and cabinet fumigation trials showed significantly lower microbial numbers on the eggshell than non-fumigated eggs during the storage period of 14 days. It was found that the values of the yolk index, albumen index and the Haugh unit of the eggs decreased during this storage time. However, those values of the fumigated eggs from both fumigation trials were found to be significantly higher than the non-fumigated eggs after the 24-h fumigation period and following storage for 5, 7 and 14 days. However, the values of the albumen index were not found to have significantly increased over 5 days of the box trial. This study is the first to report on mycofumigation activity for the purposes of reducing the presence of microorganisms on the surface of eggshells.